Odpowiedź:
a)
1/3x - 2 = x + 2
1/3x - x = 2 + 2
-2/3x = 4 /*(-3/2)
x = -3/2 * 4 = -6
b)
1 - 6/7x = 4/7
-6/7x = 4/7 - 1 /*(-7/6)
x = -3/7 * (-7/6) = 1/2
c)
6(1/4x - 2) = 18
3/2x - 12 = 18
3/2x = 18 + 12 /*2/3
x = 30 * 2/3 = 20
d)
x/6 - 1/6 = 1
1/6x = 1 + 1/6 /*6
x = 1 1/6 * 6 = 7/6 * 6 = 7
e)
-2(2x - 1) = x/3
-4x + 2 = 1/3x
-4x - 1/3x = -2
-4 1/3x = -2
-13/3x = -2 /*(-3/13)
x = 6/13
f)
2/5(3 - x) = -2
6/5x - 2/5x = -2
4/5x = -2 /*5/4
x = -2 * 5/4 = -5/2 = -2 1/2
g)
3/4(2 - 3x) = -6
3/2 - 9/4x = -6
-9/4x = -6 - 1 1/2 /*(-4/9)
x = 7 1/2 * 4/9 = 15/2 * 4/9 = 10/3 = 3 1/3
h)
1/5(x - 3) = 9 - x
1/5x - 3/5 = 9 - x
1/5x + x = 9 + 3/5
1 1/5x = 9 3/5
6/5x = 48/5 /*5/6
x = 48/5 * 5/6 = 8
i)
(0,6 + x)/2 = x + 1
0,3 + 1/2x = x + 1
1/2x - x = 1 - 0,3
-0,5x = 0,7 /:(-0,5)
x = -1,4
Szczegółowe wyjaśnienie: